2023
DOI: 10.3389/fmicb.2023.1241961
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal carriage of invasive non-typhoidal Salmonella among household members of children with Salmonella bloodstream infection, Kisangani, DR Congo

Dadi Falay,
Liselotte Hardy,
Edmonde Bonebe
et al.

Abstract: IntroductionInvasive non-typhoidal Salmonella (iNTS), mainly Salmonella Typhimurium and Salmonella Enteritidis, causes a severe burden in sub-Saharan Africa; however, its reservoir (animal or environmental) is unclear. The present study assessed healthy household members of index patients for intestinal carriage of Salmonella.MethodsIndex patients were admitted to the University Hospital of Kisangani (DR Congo), and Salmonella was grown from blood cultures. Household members were asked to provide three stool s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…There exist at least 150 serotypes of Salmonella that can cause salmonellosis or nontyphoidal enterocolitis, with the most prevalent serotypes being S. Typhimurium and S. enterica ( Falay et al ., 2023 ). Transmission is usually caused by eating or drinking water tainted with animal excrement rather than human excrement ( Teklemariam et al ., 2023 ).…”
Section: Nomenclaturementioning
confidence: 99%
“…There exist at least 150 serotypes of Salmonella that can cause salmonellosis or nontyphoidal enterocolitis, with the most prevalent serotypes being S. Typhimurium and S. enterica ( Falay et al ., 2023 ). Transmission is usually caused by eating or drinking water tainted with animal excrement rather than human excrement ( Teklemariam et al ., 2023 ).…”
Section: Nomenclaturementioning
confidence: 99%
“…Most of these isolates were genetically similar to Typhimurium and Enteritidis isolates obtained from blood cultures in Kisantu Hospital. Furthermore, previous studies (Burkina Faso, DRC) showed among nontyphoidal Salmonella a tendency toward household clustering (Im et al, 2016;Post et al, 2019;Falay et al, 2023). We hypothesized that sampling a larger community closer to Kisantu Hospital would allow for a better study of the concordance between blood and stool culture iNTS isolates and their occurrence in households.…”
Section: Introductionmentioning
confidence: 97%